Public Perceptions of the Economic Impacts of Government Funded Events (Journal of Entrepreneurship and Business, 2020)
National yearly events that are publicly funded often turn into large events that are appealing to the public and therefore need to benefit the community and society at large. While the government’s role in organising or hosting public celebrations is to foster and enhance the spirit of patriotism, love for the country, strengthen unity and national integration among the people, others may argue that these celebrations are a waste of public funds which could be better spent on the economic development, repair and provision of infrastructure and improving social conditions in the state. This paper aims to examine public perceptions at the locality of the event and surroundings on the economic impact of these events. The study covered two major state events celebrated in Sarawak, the Governor’s birthday and Malaysia Day, organised and funded by the State Protocol and Public Relations Unit of the Sarawak Chief Minister’s Office. A self-administered questionnaire was developed to survey the attendees of two celebratory events via convenience sampling. The findings from the survey found that the public perceived these events could positively support the locality in gaining temporary employment, support local trade, revive the local economy, increase hotel occupancy, and provide opportunities for future employment. However, the study further found that such events failed to create permanent employment and extend shopping hours in the event locality. Overall, it was shown that while national celebrations are perceived as events that benefit the public economically, there are concerns regarding the funding of infrastructure, which could alter the public’s perception in gaining a higher overall positive perception score.
Keywords: Array; Array; Array